NURSING PROCESS: IMPLICATIONS FOR THE SAFETY OF SURGICAL PATIENTS - Fernando Riegel; Nery José de Oliveira Junior (Universidade Federal do Paraná, 2017)
The objective in this study was to reflect on the nursing process and its implications for surgical patients. This reflection is based on the theoretical premises and scientific literature on the theme. Patient safety has been discussed since the 19 th century to achieve high-quality care at hospital institutions. The Nursing Process is a methodological instrument and a valuable light-hard technology to guarantee safety in the context of the nursing practices. It should be applied qualitatively and holistically though, in line with the institutional objectives, with a view to promoting patient safety.